A novel validated quantitative estimation & stability indicating RP -HPLC method for simultaneous estimation of tolperisone HCL and etodolac in bulk and its pharmaceutical dosage formulations - T. Rama Mohan Reddy; D.V. R. N. Bhikshapathi (International Journal of Pharmacy and Analytical Research, 2022)
A rapid, sensitive and specified RP-HPLC method involving DAD detection was developed and validated for determination and quantification of Tolperisone (TOL) and Etodolac (ETD) in tablet dosage form. Chromatography was carried out on Sunsil, 250 mm x 4.6 mm i.d; 5µ particle size column using filtered and degassed mixture of Acetonitrile and phosphate buffer (pH 2.6) in the ratio of 30:70 v/v as mobile phase at a flow rate of 1 ml/min and effluents were monitored at 267 nm. The pH of the mobile phase was adjusted with the diluent. The method was validated in terms of linearity, precision, accuracy, specificity, Limit of detection, limit of quantification and stability indicating studies. The assay was linear over the concentration range for TOL: 18-42µg/mL and for ETD: 48-112 µg/mL respectively. Accuracy of the method was determined through recovery studies by adding known quantities of standard drugs to the pre analysed test solutions and was found to be between 99.27 – 101.38% within. The % RSD for both TOL & ETD was found to be 0.66 and 0.41 respectively. The stability indicating studies were all in limit and meeting the need of the quantitative analysis. The method does require less than 10 minutes as run time for analysis which enhanced to prove the adoptability of the method for routine quality control of the drugs.